Dental anxiety is related to postoperative symptoms in third molar surgery - Qiao, Feng; Zhang, Menghua; Zhang, Tingting; Zhu, Dongwang (Frontiers in Psychiatry, 2022)
Purpose: To examine the association of preoperative dental anxiety with the severity of postoperative symptoms among patients undergoing lower third molar (LM3) extraction surgery. Materials and Methods: We conducted a hospital-based prospective study with a sample size of 213 patients. All the patients underwent LM3 extraction surgery at the Stomatology Hospital of Tianjin Medical University. Preoperative dental anxiety was measured using the Dental Anxiety Scale for Third Molar Surgery (DAS-TMS) and classified into four categories: No anxiety, Some unease, Anxious, and Very anxious. The primary outcome was defined using the postoperative symptom severity scale on the seventh day after surgery. The patients’ clinical characteristics, radiologic features, and surgery-related variables were used as control variables. Bivariate analysis involved Fisher’s exact test and Kruskal–Wallis test. Multivariable logistic analysis was used to assess preoperative dental anxiety in relation to the severity of postoperative symptoms. We applied a two-piecewise regression model to examine the potential nonlinear associations. Results: The mean (SD) dental anxiety score was 10.56 (3.84). The proportion of dental anxiety was as follows: No anxiety, 7.5%; Some unease, 46.9%; Anxious, 31.0%; Very anxious, 14.6%. The multivariable-adjusted ORs with 95% CIs of postoperative symptoms were 1.00 for No anxiety, 3.63 (0.90–14.68) for Some unease, 5.29 (1.25–22.33) for Anxious, and 4.75 (1.02–22.18) for Very anxious (P for trend = 0.047). The risk of serious postoperative symptoms increased with the dental anxiety level up to 7 points (adjusted OR 1.94, 95% CI 1.12–3.74; P = 0.012). When the dental anxiety level exceeded 7 points, the level of DAS-TMS was not associated with the risk of serious postoperative symptoms (OR 0.98, 95% CI 0.88–1.08; P = 0.756). Conclusions: Findings suggest that dental anxiety is associated with a risk of serious postoperative symptoms following LM3 removal. The degree of dental anxiety in patients before LM3 extraction surgery should be of concern to clinicians.